Emission characteristics and formation mechanisms of PM2.5 from co-firing of algal biomass and coal. (October 2021) - Fei, Lingzi; Zhao, Bingtao; Liu, Jianjian; Su, Yaxin
Abstract: To address the emissions and formation of fine particulate matter (PM2.5 ) from co-firing of algal biomass ( Chlorella (Ch), Sargassum (Sa), and Enteromarpha (En) ) and pulverized coal (Huating coal), the emission characteristics were experimentally investigated using a one-dimensional tubular furnace. The results indicate that algae species, the mixing ratio, and the reaction temperature have complex impacts on PM2.5 emissions. Its emission characteristics present either single- or double-peak distribution. The higher temperature and higher biomass fraction accelerate the formation of PM2.5 during co-firing. Different from the reduction in NOx and SO2 emissions, the PM2.5 emission from algal biomass-based co-firing is higher than that of coal alone on the whole, particularly for Sa and En . For En, the maximum PM2.5 concentration occurred at 900 °C with 91.73 mg/m 3 when 20% En was co-fired with 80% coal. Meanwhile, the PM2.5 emission yield reached the peak of 553.64 ( × 10 −2 ) mg/g. For Sa, the highest PM2.5 concentration and PM2.5 emission yield appeared when 20% Sa and 80% coal were co-fired at 1000 °C, were 125.30 mg/m 3 and 354.41 ( × 10 −2 ) mg/g, respectively. For Ch, the highest PM2.5 concentration appeared when 20% Ch and 80% coal were co-fired at 1000 °C and reached 1.11 mg/m 3, but the largest PM2.5 emission yield was 3.21 ( × 10 −2 ) mg/g when 20% Ch and 80% coal were co-fired at 1100 °C. PM2.5 generated from co-firing are mainly formed by vaporization and homogeneous/heterogeneous condensation, as well as fragmentation of internal/external minerals and char particles. In addition, it also depends upon a series of reactions between the alkali metal salt and other incombustible particles. The morphological characteristics of ash residues from Ch co-fired with coal were irregular and fragmented, and the structure was relatively compact, and those for Sa and En co-fired with coal are similar, both of which are irregular massive structures with white crystal particles attached. Graphical abstract: Image 1 Highlights: PM2.5 emissions from co-firing of three typical algal biomass and coal are addressed. The effects of temperature and the mixing ratio of algae are examined. Co-firing increases rather than decreases the PM2.5 emissions from coal combustion. The possible formation mechanisms of PM2.5 are determined based on conversion pathways. The content of alkali metals in algae affects the morphology of ashes considerably.